Carbon aerogel composite material with extremely low shrinkage and method for preparing the same
Patent Information
- Application Number
- CN202410891578.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-04
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2044-07-04
AI Technical Summary
然而,气凝胶复合材料在碳化过程中的收缩依然十分显著,进一步导致了其密度增大、孔隙率降低以及隔热性能下降等问题
[0027] (1) This invention addresses the problem of significant drying shrinkage, carbon shrinkage, and cracking in carbon aerogels prepared from phenolic resin through heating curing, atmospheric pressure drying, and carbonization processes. It develops a rigid carbon foam reinforcement material with a three-dimensional core-shell framework structure. Figure 1 This method solves the aforementioned problems in the preparation process of carbon aerogels, and the core-shell framework morphology of rigid carbon foam is visible. Figure 2 The prepared carbon aerogel composite material exhibits ultra-low drying and carbonization shrinkage, and no cracks are generated at either the macroscopic or microscopic scale. Figure 3 ).
Smart Images

Figure CN118811797B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of aerogel preparation technology, specifically relating to a carbon aerogel composite material with extremely low shrinkage and its preparation method. Background Technology
[0002] Aerogels possess ultra-low density, extremely high porosity, and micro / nanoscale pore structures. These properties endow aerogels with excellent thermal insulation performance, making them one of the most promising thermal insulation materials. Depending on the application environment, various types of aerogel materials have been developed, including polymer aerogels, ceramic aerogels, and carbon aerogels. Compared to polymer and ceramic aerogels, carbon aerogels exhibit superior high-temperature resistance under inert atmospheres or vacuum conditions, with service temperatures exceeding 2000℃. Therefore, carbon aerogels play an irreplaceable role in specific high-temperature thermal protection applications. Furthermore, due to their unique pore structure, electrical conductivity, and low surface energy, carbon aerogels can also be applied in adsorption separation, electromagnetic shielding, catalyst supports, and supercapacitors, showing broad application prospects.
[0003] Carbon aerogels can be formed by carbonizing polymer aerogels, such as polyimide aerogels, polyvinyl chloride aerogels, and phenolic resin aerogels. Among these, phenolic resin aerogels have a high carbon content, making them the preferred polymer precursor for synthesizing carbon aerogels. Phenolic resin aerogels are characterized by simple preparation processes and low costs. Their preparation mainly involves synthesizing a wet phenolic resin gel via a sol-gel method, followed by drying the wet phenolic resin gel to obtain the phenolic resin aerogel. However, due to the significant capillary forces generated by solvent evaporation, the wet phenolic resin gel undergoes severe volume shrinkage during the drying process, directly leading to increased density, pore collapse, cracking, and a significant reduction in thermal insulation performance. Our previous research showed that introducing an additional thermosetting phenolic resin into the traditional linear phenolic resin and hexamethylenetetramine reactant system can significantly reduce the volume shrinkage during the drying process of the wet gel. However, when the bulk density of the solid skeleton in the wet gel is <0.1 g / cm³, the volume shrinkage becomes more severe. 3 Even at this time, it still undergoes very severe volume shrinkage, which limits the widespread application of aerogels.
[0004] To overcome this problem, combining aerogels with other reinforcing materials to prepare aerogel composites is a simple and effective method. To achieve excellent shrinkage resistance during the drying process of aerogel composites, the reinforcing materials need to have a high modulus. However, it is important to note that the phenolic resin aerogel in the composite also undergoes significant dimensional shrinkage during the subsequent carbonization process. For example, the carbonization shrinkage rate of a single phenolic resin aerogel can reach over 20%. Therefore, to avoid cracking, the reinforcing material needs to have a carbonization shrinkage rate that is compatible with that of the phenolic resin aerogel. Currently, most studies use polymer fibers as reinforcing materials, such as phenolic resin fibers, aramid fibers, and polyacrylonitrile fibers. During carbonization, the polymer fibers can shrink synergistically with the phenolic resin aerogel, thus avoiding crack formation. However, the shrinkage of aerogel composites during carbonization is still significant, further leading to problems such as increased density, decreased porosity, and reduced thermal insulation performance.
[0005] To address this issue, this invention designs and prepares a rigid carbon foam with a three-dimensional core-shell framework structure as a reinforcing material, using melamine foam as a template. The resulting rigid carbon foam reinforced material possesses designable density, rigidity, and carbonization shrinkage. Therefore, through rational design, ultra-low drying and carbonization shrinkage rates can be achieved in carbon aerogel composites. Furthermore, the obtained carbon aerogel composite material exhibits no crack formation at either the macroscopic or microscopic scale. In addition, the carbon aerogel composite material also possesses low density, low thermal conductivity, and excellent hydrophobic properties, enabling it to perform excellent thermal insulation even in humid environments. Summary of the Invention
[0006] This invention addresses the significant drying shrinkage, carbonization shrinkage, and cracking issues that occur in carbon aerogels prepared from phenolic resin through sol-gel, atmospheric pressure drying, and carbonization processes. Using soft melamine foam as a template, a rigid carbon foam with a three-dimensional core-shell framework structure is prepared. This carbon foam is then used as a reinforcing material to prepare a carbon aerogel composite material with ultra-low drying and carbonization shrinkage, hydrophobicity, and no macroscopic or microscopic cracks. Due to its extremely low shrinkage rate, the resulting carbon aerogel composite material also exhibits ultra-low density and excellent thermal insulation properties.
[0007] The technical solution of the present invention:
[0008] A method for preparing a carbon aerogel composite material with extremely low shrinkage rate specifically includes the following steps:
[0009] (1) Dissolve thermosetting phenolic resin and hexamethylenetetramine in ethylene glycol solvent to prepare a precursor solution;
[0010] (2) Melamine foam is immersed in the precursor solution in step (1), and a rigid carbon foam with a three-dimensional core-shell skeleton structure is obtained by heating, curing, drying and carbonization.
[0011] (3) Dissolve thermoplastic phenolic resin, thermosetting phenolic resin and hexamethylenetetramine in ethylene glycol solvent to prepare precursor solution;
[0012] (4) The rigid carbon foam in step (2) is immersed in the precursor solution in step (3), and carbon aerogel composite material is obtained by heating and curing, ethanol solvent replacement, atmospheric pressure drying and carbonization.
[0013] Furthermore, in the precursor solution described in step (1), the concentration of thermosetting phenolic resin is 0.002-0.02 g / ml, and the mass ratio of hexamethylenetetramine to thermosetting phenolic resin is 1:3-10.
[0014] Furthermore, the heating and curing temperature in step (2) is 100-150℃, and the time is 3-9h.
[0015] Furthermore, the atmospheric pressure drying in step (2) involves first spin-drying the cured sample, and then drying it at 100-120℃ for 6-9 hours.
[0016] Furthermore, the carbonization process described in step (2) involves heating the sample to 500-700°C in a flowing inert gas environment and holding it at that temperature for 1-2 hours to obtain rigid carbon foam.
[0017] The shell thickness, density, and mechanical properties of the rigid carbon foam obtained in step (2) can be controlled by changing the concentration of the precursor solution. The higher the solution concentration, the thicker the shell, the greater the density, and the better the load-bearing capacity of the resulting rigid carbon foam. Therefore, using the obtained rigid carbon foam as a reinforcing material can effectively suppress the shrinkage of the aerogel during the drying and carbonization process.
[0018] The rigid carbon foam with a three-dimensional core-shell skeleton structure obtained in step (2) can not only be used as a reinforcing material for carbon aerogels, but also be used to reinforce other types of aerogels, solving the common problem of severe shrinkage of aerogels during atmospheric pressure drying.
[0019] Furthermore, in the precursor solution described in step (3), the concentration of thermoplastic phenolic resin is 0.02-0.1 g / ml, the concentration of thermosetting phenolic resin is 0.002-0.03 g / ml, and the mass ratio of hexamethylenetetramine to thermoplastic phenolic resin is 1:3-10.
[0020] Furthermore, the heating and curing process described in step (4) is divided into two stages: first, it is kept at 100-120℃ for 2-4 hours, and then kept at 150-180℃ for 2-4 hours.
[0021] Furthermore, the ethanol solvent replacement process described in step (4) involves immersing the cured sample in ethanol and placing it on a heating platform at 80-100℃ for 2-3 hours, repeating this process 2-3 times.
[0022] Furthermore, the atmospheric pressure drying process described in step (4) involves placing the ethanol-replaced sample at room temperature for 6-12 hours, then drying it at 40-60°C for 6-9 hours, and finally heating it to 80°C for 6-9 hours.
[0023] Furthermore, the carbonization process described in step (4) involves heating the sample to 800-1000℃ in a flowing inert gas environment and holding it at that temperature for 1-2 hours to obtain a carbon aerogel composite material.
[0024] Furthermore, the carbon aerogel composite material has a bus shrinkage rate of <15% during the drying and carbonization process, preferably 5-10%.
[0025] Furthermore, the thermosetting phenolic resin includes modified or unmodified thermosetting phenolic resin.
[0026] The beneficial effects of this invention are:
[0027] (1) This invention addresses the problem of significant drying shrinkage, carbon shrinkage, and cracking in carbon aerogels prepared from phenolic resin through heating curing, atmospheric pressure drying, and carbonization processes. It develops a rigid carbon foam reinforcement material with a three-dimensional core-shell framework structure. Figure 1 This method solves the aforementioned problems in the preparation process of carbon aerogels, and the core-shell framework morphology of rigid carbon foam is visible. Figure 2 The prepared carbon aerogel composite material exhibits ultra-low drying and carbonization shrinkage, and no cracks are generated at either the macroscopic or microscopic scale. Figure 3 ).
[0028] (2) Rigid carbon foam reinforcing material has designable density, rigidity, and carbonization shrinkage rate. Therefore, this reinforcing material can not only serve as the reinforcing phase of the aerogel in this invention, but also is expected to solve the common problem of severe shrinkage of various types of aerogels during atmospheric pressure drying.
[0029] (3) Thanks to the ultra-low density and high rigidity of the rigid carbon foam reinforcement material, the prepared carbon aerogel composite material exhibits extremely low shrinkage rates at various reactant concentrations. Therefore, ultra-low density and excellent thermal insulation performance of the carbon aerogel composite material are achieved.
[0030] (4) Due to the low surface energy and rough nanoscale surface structure of carbon aerogel composites, they also have excellent hydrophobic properties, as can be seen in the images of their contact with water droplets. Figure 4 Therefore, carbon aerogel composites can still fully exert their excellent thermal insulation capabilities even in humid environments.
[0031] (5) Carbon aerogel composites have the advantages of simple preparation process, low cost and high efficiency. The prepared carbon aerogel composites can withstand temperatures up to 2000℃ in vacuum or inert atmosphere, so they can be used in the field of high temperature insulation. In addition, they can also be used in adsorption separation, electromagnetic shielding, catalyst support and supercapacitors, etc., and have broad application prospects. Attached Figure Description
[0032] Figure 1 Microstructure of rigid carbon foam reinforced materials
[0033] Figure 2 Microstructure of the core-shell framework of rigid carbon foam reinforced material
[0034] Figure 3 Microstructure of carbon aerogel composite materials
[0035] Figure 4 Images of carbon aerogel composite materials in contact with water droplets. Detailed Implementation
[0036] The specific embodiments of the present invention will be further described below with reference to the accompanying drawings and technical solutions.
[0037] Example 1
[0038] This embodiment describes a typical preparation method and properties of a carbon aerogel composite material, demonstrating that the rigid carbon foam reinforcing material in this invention can significantly reduce the drying and carbonization shrinkage rate of the carbon aerogel composite material during the preparation process. Specific implementation details are as follows:
[0039] (1) Dissolve 0.2g of powdered thermosetting boron phenolic resin and 0.04g of hexamethylenetetramine in 40ml of ethylene glycol solvent by magnetic stirring to obtain a precursor solution;
[0040] (2) Immerse the melamine foam in the precursor solution and place it in a sealed container, then cure it in an oven at 120°C for 6 hours;
[0041] (3) Shake off the solution inside the foam and then dry it in an oven at 120°C for 8 hours;
[0042] (4) The dried sample was heated to 650℃ and held for 1 hour in a flowing argon atmosphere to obtain rigid carbon foam. The obtained rigid carbon foam has a three-dimensional core-shell framework structure, such as... Figure 1 and 2 As shown. Its density, compressive modulus, and shell thickness are 0.009 g / cm³. 3 276.5 kPa and 0.35 μm;
[0043] (5) Dissolve 2g of powdered thermoplastic phenolic resin, 0.57g of thermosetting boron phenolic resin and 0.4g of hexamethylenetetramine in 40ml of ethylene glycol solvent by magnetic stirring to obtain a precursor solution;
[0044] (6) The rigid carbon foam prepared in step (4) is immersed in the precursor solution and placed in a sealed container. Then it is cured in an oven at 120°C for 3 hours and in an oven at 180°C for 3 hours to obtain a wet gel sample.
[0045] (7) The cured wet gel sample was immersed in 95% industrial ethanol for solvent replacement and placed on a heating platform at 100°C for 2 hours. This process was repeated 3 times.
[0046] (8) The ethanol-replaced sample was left to stand at room temperature for 12 hours, then dried in an oven at 50°C for 9 hours, and finally dried at 80°C for 6 hours.
[0047] (9) The dried sample was heated to 800℃ in a flowing argon atmosphere and kept at that temperature for 1 hour to obtain a carbon aerogel composite material.
[0048] The microstructure of the obtained carbon aerogel composite material is as follows Figure 3 As shown in the figure, the rigid carbon foam reinforcement material and the carbon aerogel skeleton particles are clearly visible, and no cracks caused by inconsistent carbonization shrinkage are observed at the interface between the two. The obtained carbon aerogel composite material has ultra-low drying and carbonization shrinkage rates, with linear shrinkage rates of 0.6% and 5.9%, respectively. The carbon aerogel composite material also has ultra-low density and thermal conductivity, with values of 0.047 g / cm³. 3 And 0.028 W / (m·K). Furthermore, the compressive strength and water contact angle of the carbon aerogel composite were 94.4 kPa and 147.5°, respectively.
[0049] Comparative Example 1
[0050] This comparative example is compared with Example 1 to demonstrate that the carbon aerogel composite material prepared using soft melamine foam as a reinforcing material, and the carbon aerogel prepared without a reinforcing material, exhibit very large drying shrinkage and carbonization shrinkage. For greater comparability and fairness, the precursor solution concentration and preparation conditions used in this comparative example are identical to those in Example 1. Specific implementation methods are as follows:
[0051] (1) Dissolve two portions of powdered thermoplastic phenolic resin 2g, thermosetting boron phenolic resin 0.57g and hexamethylenetetramine 0.4g in 40ml of ethylene glycol solvent by magnetic stirring to obtain two precursor solutions of the same concentration.
[0052] (2) Immerse the melamine foam in the first precursor solution and place it in a sealed container. Pour the second precursor solution directly into the sealed container. Then, cure the two sealed containers in an oven at 120°C for 3 hours and in an oven at 180°C for 3 hours to obtain a wet gel sample.
[0053] (3) The cured wet gel sample was immersed in 95% industrial ethanol for solvent replacement and placed on a heating platform at 100°C for 2 hours. This process was repeated 3 times.
[0054] (4) The ethanol-replaced sample was left to stand at room temperature for 12 hours, then dried in an oven at 50°C for 9 hours, and finally dried at 80°C for 6 hours.
[0055] (5) The dried sample was heated to 800℃ in a flowing argon atmosphere and kept at that temperature for 1 hour to obtain carbon aerogel and its composite material.
[0056] Experimental results show that the carbon aerogels prepared by both methods in Comparative Example 1 underwent severe shrinkage during drying, and the shrinkage deformation was highly uneven. The dried samples could not maintain their original shape, making it impossible to calculate the specific linear shrinkage rate. Furthermore, the carbonization shrinkage rate of both samples exceeded 20%. Therefore, in this comparative example, the prepared carbon aerogel and melamine foam-reinforced carbon aerogel composite material not only experienced severe shrinkage and deformation during drying, but also exhibited significant shrinkage during carbonization, thus demonstrating the beneficial effect of this invention in effectively reducing the shrinkage rate of carbon aerogel composite material preparation.
[0057] Example 2
[0058] This embodiment describes a method for preparing carbon aerogel composite materials with reactant concentrations different from those in Example 1. Specifically, compared to Example 1, the reactant concentration of the rigid carbon foam reinforcement material is reduced, while the reactant concentration of the subsequent carbon aerogel composite material is increased. The specific implementation method is as follows:
[0059] (1) Dissolve 0.12g of powdered thermosetting boron phenolic resin and 0.024g of hexamethylenetetramine in 40ml of ethylene glycol solvent by magnetic stirring to obtain a precursor solution;
[0060] (2) Immerse the melamine foam in the precursor solution and place it in a sealed container, then cure it in an oven at 120°C for 6 hours;
[0061] (3) Shake off the solution inside the foam and then dry it in an oven at 120°C for 8 hours;
[0062] (4) The dried sample was heated to 650℃ and held for 1 hour in a flowing argon atmosphere to obtain rigid carbon foam. The density, compressive modulus, and shell thickness of the rigid carbon foam were 0.0067 g / cm³. 3 221.1 kPa and 0.2 μm;
[0063] (5) Dissolve 2.8g of powdered thermoplastic phenolic resin, 0.8g of thermosetting boron phenolic resin and 0.56g of hexamethylenetetramine in 40ml of ethylene glycol solvent by magnetic stirring to obtain a precursor solution;
[0064] (6) The rigid carbon foam prepared in step (4) is immersed in the precursor solution and placed in a sealed container. Then it is cured in an oven at 120°C for 3 hours and in an oven at 180°C for 3 hours to obtain a wet gel sample.
[0065] (7) The cured wet gel sample was immersed in 95% industrial ethanol for solvent replacement and placed on a heating platform at 100°C for 2 hours. This process was repeated 3 times.
[0066] (8) The ethanol-replaced sample was left to stand at room temperature for 12 hours, then dried in an oven at 50°C for 9 hours, and finally dried at 80°C for 6 hours.
[0067] (9) The dried sample was heated to 800℃ in a flowing argon atmosphere and kept at that temperature for 1 hour to obtain a carbon aerogel composite material.
[0068] The drying and carbonization linear shrinkage rates of the obtained carbon aerogel composite material were 1.5% and 11.5%, respectively. It can be seen that, due to the lower modulus of the reinforcing material in this embodiment, the drying and carbonization shrinkage rates of the carbon aerogel composite material are slightly greater than those in Example 1. Nevertheless, the results in this embodiment are still significantly better than those in Comparative Example 1.
[0069] In this invention, a rigid carbon foam with ultra-low density and high rigidity was designed and prepared as a reinforcing material for aerogel. Through the reinforcement of the rigid carbon foam, a carbon aerogel composite material with ultra-low drying and carbonization shrinkage rates was successfully prepared. Furthermore, the rigid carbon foam reinforcing material also possesses a carbonization shrinkage rate compatible with that of the aerogel, thus the prepared carbon aerogel composite material exhibits no crack formation at either the macroscopic or microscopic scale. Due to its excellent anti-shrinkage properties, the carbon aerogel composite material has ultra-low density and thermal conductivity. In addition, due to its low surface energy and rough surface structure, the carbon aerogel composite material also exhibits excellent hydrophobic properties, resulting in excellent thermal insulation performance even in humid environments. The carbon aerogel composite material has broad application prospects, such as high-temperature thermal protection, adsorption separation, electromagnetic shielding, catalyst support, and supercapacitors. This invention is not limited to the above embodiments; the proportions of each phase can be increased as needed, provided they do not exceed the scope of this invention.
Claims
1. A method for preparing a carbon aerogel composite material with extremely low shrinkage, characterized in that, Specifically, the steps include the following: (1) Dissolve thermosetting phenolic resin and hexamethylenetetramine in ethylene glycol solvent to prepare a precursor solution; (2) Melamine foam is immersed in the precursor solution in step (1), and a rigid carbon foam with a three-dimensional core-shell skeleton structure is obtained by heating, curing, drying and carbonization. (3) Dissolve thermoplastic phenolic resin, thermosetting phenolic resin and hexamethylenetetramine in ethylene glycol solvent to prepare a precursor solution; (4) The rigid carbon foam in step (2) is immersed in the precursor solution in step (3), and carbon aerogel composite material is obtained by heating and curing, ethanol solvent replacement, atmospheric pressure drying and carbonization.
2. The method for preparing a carbon aerogel composite material with extremely low shrinkage rate according to claim 1, characterized in that, In the precursor solution described in step (1), the concentration of thermosetting phenolic resin is 0.002-0.02 g / ml, and the mass ratio of hexamethylenetetramine to thermosetting phenolic resin is 1:3-10.
3. The method for preparing a carbon aerogel composite material with extremely low shrinkage rate according to claim 1, characterized in that, The heating and curing temperature in step (2) is 100-150℃ and the time is 3-9h; the atmospheric pressure drying is to first spin-dry the cured sample, and then dry it at 100-120℃ for 6-9h.
4. The method for preparing a carbon aerogel composite material with extremely low shrinkage rate according to claim 1, characterized in that, The carbonization process described in step (2) involves heating the sample to 500-700℃ in a flowing inert gas environment and holding it at that temperature for 1-2 hours to obtain rigid carbon foam.
5. The method for preparing a carbon aerogel composite material with extremely low shrinkage rate according to claim 1, characterized in that, The shell thickness, density, and mechanical properties of the rigid carbon foam obtained in step (2) can be controlled by changing the concentration of the precursor solution. The higher the solution concentration, the thicker the shell, the greater the density, and the better the load-bearing capacity of the rigid carbon foam.
6. The method for preparing a carbon aerogel composite material with extremely low shrinkage rate according to claim 1, characterized in that, In the precursor solution described in step (3), the concentration of thermoplastic phenolic resin is 0.02-0.1 g / ml, the concentration of thermosetting phenolic resin is 0.002-0.03 g / ml, and the mass ratio of hexamethylenetetramine to thermoplastic phenolic resin is 1:3-10.
7. The method for preparing a carbon aerogel composite material with extremely low shrinkage rate according to claim 1, characterized in that, The heating and curing process described in step (4) is divided into two stages: first, the sample is kept at 100-120℃ for 2-4 hours, and then kept at 150-180℃ for 2-4 hours; the ethanol solvent replacement process is to immerse the cured sample in ethanol and place it on a heating platform at 80-100℃ for 2-3 hours, and repeat this process 2-3 times.
8. The method for preparing a carbon aerogel composite material with extremely low shrinkage rate according to claim 1, characterized in that, The atmospheric pressure drying process in step (4) involves placing the ethanol-replaced sample at room temperature for 6-12 hours, then drying it at 40-60℃ for 6-9 hours, and finally heating it to 80℃ for 6-9 hours. The carbonization process involves heating the sample to 800-1000℃ in a flowing inert gas environment and holding it for 1-2 hours to obtain a carbon aerogel composite material.
9. A carbon aerogel composite material with extremely low shrinkage rate prepared by any one of the preparation methods according to claims 1-8.
10. A carbon aerogel composite material with extremely low shrinkage rate prepared by the preparation method according to claim 1, characterized in that, The carbon aerogel composite material exhibits a total shrinkage rate of <15% during the drying and carbonization process.